2013
DOI: 10.3109/14767058.2013.837879
|View full text |Cite
|
Sign up to set email alerts
|

Correlation ofUGT1A1TATA-box polymorphism and jaundice in breastfed newborns-early presentation of Gilbert's syndrome

Abstract: This study provides evidence that UGT1A1 TATA-box polymorphism is an important risk factor for developing jaundice in term breastfed newborns, presented as either early non-physiologic hyperbilirubinemia or breast milk jaundice. These results further support the original Odell's idea of neonatal jaundice as an early presentation of GS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Currently, the correlation between UGT1A1 polymorphisms and risk of neonatal hyperbilirubinemia mainly focuses on the TATA box in the promoter region and the coding region [ 27 , 28 ]. It was reported that the coding region mutation of the UGT1A1 gene was highly prevalent in Asia, with G211A as the predominant type of mutations [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the correlation between UGT1A1 polymorphisms and risk of neonatal hyperbilirubinemia mainly focuses on the TATA box in the promoter region and the coding region [ 27 , 28 ]. It was reported that the coding region mutation of the UGT1A1 gene was highly prevalent in Asia, with G211A as the predominant type of mutations [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical significance of this finding remains unclear as the infants in these studies had either subclinical or only mild/moderate hyperbilirubinemia (27). GS has also been associated with the jaundice of inadequate breastfeeding with weight loss (“breastfeeding jaundice”) (42,43) and with breast milk jaundice (see Breast milk jaundice ) (44,45). …”
Section: Inherited Disorders Of Bilirubin Clearancementioning
confidence: 99%
“…Neonatal jaundice is associated with a variety of physiologic and pathologic conditions 1 . Gene variants involving the production and metabolism of bilirubin are risk factors of neonatal jaundice – including glucose-6-phosphate dehydrogenase (G6PD) 2 , blood group 3 , heme oxygenase (HO)−1 4 , hepatic solute carrier organic anion transporter 1B1 (SLCO1B1) 5 , and UDP-glucuronosyltransferase 1A1 (UGT1A1) 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%